THE ROLE OF READING IN LANGUAGE FLUENCY - Akhmedov Jahongirbek (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Reading is widely recognized as a fundamental component in the development of language fluency. This article explores how consistent and purposeful reading contributes to vocabulary expansion, grammatical competence, and overall communicative ability in a second language. Drawing on theoretical perspectives and practical observations, the paper highlights the cognitive processes involved in reading and their direct influence on language acquisition. The study also discusses effective reading strategies and their implications for learners and educators. Ultimately, the article argues that reading serves as a cornerstone for achieving fluency by providing rich linguistic input and reinforcing language structures in meaningful contexts.